KONTRIBUSI PEMANFAATAN FASILITAS BELAJAR, IKLIM ORGANISASI DAN ETOS KERJA DOSEN TERHADAP EFEKTIVITAS PEMBELAJARAN DI SEKOLAH TINGGI ILMU TARBIYAH ( STIT ) AL – HIKMAH TEBING TINGGI - Yassir Husein Pardede; Husnul Fadillah; Fitriani Fitriani; Irma Safitri; Dedy Darmansyah Pasaribu (Jurnal Prodi Fakultas Ekonomi-UISU, 2022)
The problem of this research is: How does working facilities, organizational climate and work ethic lecturer on the effectiveness of learning. This study aims to determine the effect of work facilities, organizational climate and work ethic of lecturers on the effectiveness of learning. With the Total Sampling technique, the sample in this study was 55 people. Learning facilities partially have a positive effect on the effectiveness of learning; Organizational climate partially has a positive effect on the effectiveness of learning; The work ethic partially has a positive effect on the effectiveness of learning; Learning facilities, organizational climate and work ethic of lecturers have a positive and significant effect on the effectiveness of learning.